Recent Progress in Plant Taxonomy and Floristic Studies (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Taxonomy, floristic studies, biosystematics, classical taxonomy, and modern taxonomic advances; phylogenomics, phylogenetics, and biogeography, including phylogeography; and the description of well-documented new taxonomic taxa, monographs, and taxonomic revisions. It incorporates data from classical morphology (including both macro and micro morphology), molecular study, anatomy and ecology, distribution, molecular evolution, evolutionary development, population biology, conservation biology, evolutionary ecology, paleobiology, and related methods and theories in recent development in systematics and floristic studies.